Nutritive value and in-situ rumen degradation of selected livestock feeds - Chana, Z. M.; Abubakar, M.; Kolo, U. M.; Yakubu, A. K.; Abubakar, A. D. (Nigerian Journal of Animal Science, 2025)
Astudy was conducted to evaluate the nutritive value and in situ ruminal degradation of maize bran (MB), cotton seed cake (CSC), sorghum pinnacle (SP) and poultry litter (PL) using three pistulated rams. The rumen degradability of these feedstuffs were studied at 0, 3, 6, 12, 24, 48, 72 and 96 hours incubation periods using the equation Y = a + b (1 – e-ct ). The results of the chemical composition of these feedstuffs were at a higher nutrient profile especially CSC and PL. The dry matter losses from the nylon bags of the various feedstuffs were significantly (P<0.05) different across them and major losses occurred between 12 to 72 hours incubation time. There was a significant (P<0.05) difference in degradability characteristics across the various feedstuffs. Solubility (a) of the dry matter ranged from 28.02% for SP to 42.05% for PL. The amount of dry matter degraded in the rumen with time (b) is highest for PL (55.67%) and lowest in SP (25.07%). While the degradation rate (c) ranged from 0.003/h for SP to 0.021/h for PL and potential degradability was 85.78, 97.98, 53.09 and 97.72% for MB, CSC, SP and PL respectively and was the reflection of their nutritive value. The effective rumen degradability of these various feedstuffs were significantly (P<0.05) different between the treatment groups and at each outflow rate. An increase in the outflow rate from 0.02 to 0.08/h led to corresponding decrease in the degradability of the various feedstuffs. It was concluded that effective degradability of poultry litter, cotton seed cake and maize bran were exceptional at all the four outflow rates used, hence confirms the superiority of these feeds over sorghum pinnacle.